Identification of fungi isolated from commercial bumblebee colonies - Chow,LJ; Nesbit,ML; Hill,T; Tranter,C; Evison,SEF; Hughes,WOH; Graystock,P (PeerJ, 2024)
Fungi can have important beneficial and detrimental effects on animals, yet our understanding of the diversity and function of most bee-associated fungi is poor. Over 2 million bumblebee colonies are traded globally every year, but the presence and transport of viable fungi within them is unknown. Here, we explored whether any culturable fungi could be isolated from commercial bumblebee nests. We collected samples of various substrates from within 14 bumblebee colonies, including the honey, honey cup wall, egg cup wall, and frass then placed them on agar and recorded any growth. Fungal morphotypes were then subcultured and their ITS region sequenced for identification. Overall, we cultured 11 fungal species from the various nest substrates. These included both pathogenic and non-pathogenic fungi, such as Aspergillus sp., Penicillium sp., and Candida sp. Our results provide the first insights into the diversity of viable fungal communities in commercial bumblebee nests. Further research is needed to determine if these fungi are unique to commercial colonies or prevalent in wild bumblebee nests, and crucially to determine the ecological and evolutionary implications of these fungi in host colonies.